If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-2r)(8) + (25) = 0 Remove parenthesis around (-2r) -2r(8) + (25) = 0 Reorder the terms for easier multiplication: -2 * 8r + (25) = 0 Multiply -2 * 8 -16r + (25) = 0 -16r + 25 = 0 Reorder the terms: 25 + -16r = 0 Solving 25 + -16r = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + -16r = 0 + -25 Combine like terms: 25 + -25 = 0 0 + -16r = 0 + -25 -16r = 0 + -25 Combine like terms: 0 + -25 = -25 -16r = -25 Divide each side by '-16'. r = 1.5625 Simplifying r = 1.5625
| 4/2-4/5= | | 9=8m+9 | | -3(-4-6y)+7(-4+5)=-8 | | 4/21*(145-y) | | X+(-4)+6x=3x+(-1)+5 | | 5-(x+7)=5x-8 | | 3+(y+2)+2(y-3)=-15 | | -3x=7-13 | | 4+ln(x+3)=6 | | 15=3r-6 | | f(-5)+f(2)=10 | | 7g-12=23 | | 2y=10-3x | | 79430.28=r(629.4-r) | | 500=9x+3x | | 49.5=r(15-r) | | 8(y-10)=26 | | 2y^2-18x+2y-67=0 | | 5f+11=26 | | 2d+7=15 | | 3e-5=19 | | 5x^2+20xy-40= | | 2x+2(2x+1)+(-3x)+(-6)=4x+3+(-3)+x+8 | | x^4-8x^3-2x^2+56x+48=0 | | 4x+3=-4y+3 | | .5x+4=.667x | | x^2+Y^2-10x+16y+85=0 | | 5(u-8)-4=-6(-2u+9)-3u | | 5(u-8)-4=-6(-2+9)-3u | | 5u-40-4=12u-54-3u | | x(2x-3)(6x-1)= | | 5+(-9)+13= |